Nd/TiO2 Anatase-Brookite Photocatalysts for Photocatalytic Decomposition of Methanol - Kočí, Kamila; Troppová, Ivana; Reli, Martin; Matějová, Lenka; Edelmannová, Miroslava; Drobná, Helena; Dubnová, Lada; Rokicińska, Anna; Kuśtrowski, Piotr; Čapek, Libor (Frontiers in Chemistry, 2018)
Neodymium enriched TiO2 anatase-brookite powders were prepared by unconventional method via using pressurized hot fluids for TiO2 crystallization and purification. The photocatalysts were tested in the CH3OH photocatalytic decomposition and they were characterized with respect to the textural (nitrogen adsorption), structural (XRD, XPS and Raman spectroscopies), chemical (XRF) and optical (DR UV–Vis spectroscopy) and photoelectrochemical measurement. All prepared materials were nanocrystalline, had biphasic (anatase- brookite) structure and relatively large specific surface area (125 m2.g-1). The experimental results indicate that the doping of neodymium on TiO2 photocatalysts significantly enhances the efficiency of photocatalytic reaction. The photocatalytic activity increased with increasing portion of hydroxyl oxygen to the total amount of oxygen species. It was found that the optimal dosage of 1 wt% Nd in TiO2 achieved the increasing of hydrogen production by 70 % in comparison with pure TiO2. The neodymium doped on the TiO2 surface act as sites at which electrons accumulate. The higher efficiency of photocatalytic process was achieved due to improved electron-hole separation on the modified TiO2 photocatalysts. This result was confirmed by electrochemical measurements, the most active photocatalysts proved the highest photocurrent responses.